2013
DOI: 10.12691/education-1-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Students’ Beliefs is one of the Aspects of Competence Oriented System of Mathematics Teachers’ Methodical Preparation

Abstract: The article analyzes the results of determination of students'-future math teachers' beliefs about the state of their preparation for future professional activities. The measurement and qualitative analysis of students' beliefs concerning their future profession is an important pedagogical problem. The measurement analysis of Ukrainian students' value beliefs (future Mathematics teachers) with the help of the methods proposed in the TEDS-M project are compared with the results of analogical investigations in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…In their study with Turkish teachers with a year more of experience than those in the present study, it was found that that teachers had more static beliefs about the nature of mathematics, but more constructivist beliefs about learning mathematics. On the other hand, Tarasenkova and Akulenko (2013), in examining the beliefs of Ukrainian teacher candidates with the same data collection tool, obtained similar results about mathematics achievement while detecting more traditional beliefs about the nature of mathematics, likewise in contrast to our own findings.…”
Section: Discussionsupporting
confidence: 74%
“…In their study with Turkish teachers with a year more of experience than those in the present study, it was found that that teachers had more static beliefs about the nature of mathematics, but more constructivist beliefs about learning mathematics. On the other hand, Tarasenkova and Akulenko (2013), in examining the beliefs of Ukrainian teacher candidates with the same data collection tool, obtained similar results about mathematics achievement while detecting more traditional beliefs about the nature of mathematics, likewise in contrast to our own findings.…”
Section: Discussionsupporting
confidence: 74%
“…The applied aspects of math logic are also worth focusing on in the process of mathematical and methodical training of future Mathematics teachers. Since they form, as our research reveals [26,27], "problem areas" in students' mathematical and methodical training and predetermine their beliefs about the nature of Mathematics.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (Albion and Ertmer [22;23]; Block and Hazelip [24], Calderhead [25]) underline that practicing teachers' beliefs influence strongly implementation and effectiveness of any innovative instruction technique. In our research (Tarasenkova and Akulenko [19]) we analyse future Mathematics teachers' beliefs (about the nature of Mathematics; about learning Mathematics; about students' mathematics abilities; about students' preparedness for teaching Mathematics using contemporary instructional approaches). We state that students' beliefs strongly influence their self-confidence and self-estimation, the level of the preparedness for teaching Mathematics using innovations.…”
Section: Background Of the Studymentioning
confidence: 99%